Recovery from bone loss, diminished mineral density and strength in mice after treatment with steroidal and nonsteroidal anti-inflammatory drugs by injection of exosomes enriched with agomir miRNAs: Anti-inflammatory drugs impact on bones - Lehmann, Tomasz P.; Pruszyńska-Oszmałek, Ewa; Kołodziejski, Paweł; Wojtków, Magdalena; Pezowicz, Celina; Szybowicz, Mirosław; Jagodziński, Paweł P.; Nowicki, Marek; Trzaskowska, Aleksandra; Mielcarek, Sławomir; Głowacki, Maciej (Journal of Medical Science, 2019)
The project “Recovery from bone loss, diminished mineral density and strength in mice after treatment with steroidal and nonsteroidal anti-inflammatory drugs by injection of exosomes enriched with agomir miRNAs” is an animal experiment project, and an attempt to apply small RNA strands to reverse the harmful effects of anti-inflammatory drugs. Patients chronically treated with an anti-inflammatory drug suffer from musculoskeletal side effects, including reversed mineralisation and disabled bone fracture healing. The aims of the study are to measure changes in bone mineral density and bone strength in mice treated with methylprednisolone or diclofenac in combination with treadmill exercise. The reversal of the negative effects of these drugs will be assayed using modified miRNA agomir. Bones obtained from the treated mice will be analysed using micro-CT, dynamic mechanical analysis (DMA), nanoindentation, Raman spectroscopy and gene expression. We expect to find specific miRNA counteracting the demineralisation of the mice bones caused by methylprednisolone or diclofenac.
Keywords: methylprednisolone; diclofenac; miRNA; bone; exercise; bone strenght